Population genetics and genomics of Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) associated with Eucalyptus in Brazil - Sato, Frederico Nanini Souza (2025)
Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) is one of the most damaging native defoliators of Eucalyptus plantations in Brazil. This thesis employs a multidisciplinary approach, integrating data on genetic diversity, ecological niche modeling, genome assembly, and whole-genome sequencing (WGS) to investigate the population structure, dispersal patterns, and adaptive potential of this pest. The goal is to establish an evolutionary and genomic framework to support T. arnobia management (IRM), especially in light of the anticipated deployment of new technologies for pest control in Brazilian silviculture. Mitochondrial multilocus analyses revealed 22 haplotypes structured into three geographically restricted haplogroups, with high φ ST values indicating historical isolation and limited maternal gene flow. Species distribution modeling suggested high climatic suitability for T. arnobia across most of Brazil, as well as in parts of Africa, Asia, and Oceania, with isothermality and precipitation emerging as key predictors. The genome sequencing produced a 454.58 Mb nuclear draft genome (read N50 = 6,855 bp), providing the first genomic reference for a species in the Thyrinteina genus. Cytogenetic data, including karyotyping, further supported the integrity of the genome. WGS of 135 individuals from nine populations yielded 17.4 million SNPs, of which 111 individuals passed filtering and were included in the final dataset. PCA and NGSAdmix analyses revealed four genetically distinct nuclear clusters that corresponded well with the mitochondrial groupings. PCA analysis and limited admixture among clusters suggest strong population structure and restricted gene flow. Selective sweep analysis using SweepFinder2 identified genomic regions under positive selection, including loci related to detoxification (cytochrome P450), genome maintenance (SETMAR-like), and metabolic regulation (HXT4-like). These findings provide functional insights into local adaptation in the T. arnobia population. Altogether, the results underscore the need for region-specific insect management strategies, given the genetic structuring and adaptive divergence of T. arnobia populations. This thesis delivers foundational resources for evolutionary monitoring and sustainable pest control in Brazilian forestry.